2022
DOI: 10.24136/oc.2022.021
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency-based non-linear approach to analyzing implied volatility transmission across global financial markets

Abstract: Research background: The contagious impact of the COVID-19 pandemic has heightened financial market's volatility, nonlinearity, asymmetric and nonstationary dynamics. Hence, the existing relationship among financial assets may have been altered. Moreover, the level of investor risk aversion and market opportunities could also alter in the pandemic. Predictably, investors in the heat of the moment are concerned about minimizing losses. In order to determine the level of hedge risks between implied volatilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Accordingly, the roles of exchange rate and interest rate can be factored to contribute to the understanding of the macroeconomic modelling. Considering the rapid fluctuations in financial time series leading to their nonlinearities, analyses can also be performed using robust decomposition techniques coupled with the quantification of the amount of information that flows through the macroeconomic variables [ [76] , [77] , [78] , [79] , [80] , [81] , [82] ]. The sample period is limited to August 2021 due to limited data availability for some variables for the G8 nations but enough for the subject matter to be investigated.…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 99%
“…Accordingly, the roles of exchange rate and interest rate can be factored to contribute to the understanding of the macroeconomic modelling. Considering the rapid fluctuations in financial time series leading to their nonlinearities, analyses can also be performed using robust decomposition techniques coupled with the quantification of the amount of information that flows through the macroeconomic variables [ [76] , [77] , [78] , [79] , [80] , [81] , [82] ]. The sample period is limited to August 2021 due to limited data availability for some variables for the G8 nations but enough for the subject matter to be investigated.…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 99%
“…that have the potential to make these dairy prices more volatile. On the one hand, the post-2020 time period can be associated with increasing levels of risk aversion (Boateng et al, 2022), whereas other authors point out increased price volatility and interconnectedness among financial markets starting in early 2020 (Zeng et al, 2023). In our study, we employ the Granger causality test for the causal effects of speculation on price movements and the GARCH model to test for its impact on conditional return volatility including the post-2020 timeframe.…”
Section: Introductionmentioning
confidence: 98%
“…The most pronounced effect of the S&P 500 index decline is the expansion of the unemployment rate. Nonetheless, investors need to consider the anticipated developments of the unemployment rate (Hu et al 2018;Jiao and Ye 2022), interest rate (Bhar et al 2015;Fougue and Saporito 2018), inflation rate (Pineiro-Chousa et al 2018;Golitsis et al 2022;Soydemir et al 2017), and volatility index (Belas and Rahman 2023;Boateng et al 2022;Biardi et al 2020), when deciding whether to invest in the S&P 500 stock index as also confirmed by the specified studies. Moreover, investors should also access the historical data, trading volumes, and some other relevant market indicators, e.g., evaluate the risk characteristics of the active strategy compared to the passive index.…”
mentioning
confidence: 94%